2007
DOI: 10.1155/2007/93431
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Prevents Traumatic Brain Injury-Induced Intestinal Nuclear Factor kappa B Activation and Proinflammatory Cytokines Expression in Male Rats

Abstract: We have previously shown that traumatic brain injury (TBI) can induce an upregulation of nuclear factor kappa B (NF-κB) and proinflammatory cytokines in the gut, which play an important role in the pathogenesis of acute gut mucosal injury mediated by inflammation. In this work, we investigated whether progesterone administration modulated intestinal NF-κB activity and proinflammatory cytokines expression after TBI in male rats. As a result, we found that administration of progesterone following TBI could decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 32 publications
1
37
0
1
Order By: Relevance
“…Protective effects of progesterone in the acutely injured brain include decreased neuroinflammation and secondary injury through multiple pathways, including NFκB and mitogen-active protein kinases [40,41,42,43]. Further, progesterone decreases reactive oxygen species through its effects on mitochondria in multiple tissue types, including the brain [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Protective effects of progesterone in the acutely injured brain include decreased neuroinflammation and secondary injury through multiple pathways, including NFκB and mitogen-active protein kinases [40,41,42,43]. Further, progesterone decreases reactive oxygen species through its effects on mitochondria in multiple tissue types, including the brain [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…intestinal mucosal structure [17,18]. However, until now no study was found in the literature to investigate the effects of progesterone on intestinal inflammatory response and mucosa structure alterations after SAH.…”
Section: Introductionmentioning
confidence: 99%
“…Our research provided direct evidence that nongenomic effect of progesterone could restrain iNOS activation mediated by P38MAPK signal pathway. This effect resulted in a decrease in serum NO concentration in infectious women, caused anti-inflammation, and played a certain role in asymptomatic infections [26] . Although nongenomic effect of progesterone in asymptomatic infections is limited, it can provide a piece of clue to elucidate the phenomenon.…”
Section: Discussionmentioning
confidence: 99%